The Mays of Ventadorn - Merwin, W. S. 1927-2019 (National Geographic, 2002)
Poet W. S. Merwin interweaves his own reminiscences with, "a chronicle of the lordly 12th-century bards who once ruled a world where kings were poets and poets kings."
Keywords: Bernart <de Ventadorn, 12th cent>; Merwin, W. S <1927-> -- (William Stanley) -- Travel -- France -- Limousin; Merwin, W. S <1927-> -- (William Stanley) -- Travel -- France, Southwest; Troubadours; Frankreich; Château de Ventadour Site (France); France, Southwest -- Description and travel; Limousin (France) -- Description and travel